A8.7 Functional Impairment in an Animal Model for Rheumatoid Arthritis Assessed as Changes in Gait is Due to Joint Destruction But Not Synovial Inflammation Per Se. (25th February 2013) - Bauer, Gregor; Willburger, Martin; Aschauer, Constantin; Jelinek, Aurica; Shvets, Tetyana; Niederreiter, Birgit; Smolen, Josef; Redlich, Kurt; Hayer, Silvia
Abstract : Objective: To investigate the individual impact of synovial inflammation, subchondral bone erosion or cartilage damage on functional impairment in an animal model of Rheumatoid Arthritis (RA). Methods: We analysed gait profiles in human tumour necrosis factor transgene (hTNFtg) animals, using the video-based Catwalk gait analysis system (from Noldus, Netherlands). In this system, mice run along an illuminated glass plate. A digital camera measures light emissions resulting from the contact of paws on the glass plate. We evaluated gait profiles at different time points of disease (6, 10, 15 week of age) in hTNFtg animals. Wildtype littermates served as controls. Bodyweight and clinical signs of arthritis including paw swelling and grip strength were also evaluated. To investigate whether gait changes are pain related, we treated hTNFtg animals with diclofenac (50 mg/kg, i.p.) at week 10 and week 15 after birth and analysed gait profiles before, as well as 1 h and 3 h after treatment. To investigate reversibility in impaired gait profils, we treated hTNFtg mice with anti-TNF (Infliximab 10 mg/kg body weight, 2× per week) for 5 weeks starting 6 and 10 weeks after birth. To analyse inflammatory joint destruction, we quantitatively assessed the extend of synovial inflammation, subchondral bone erosion and cartilage damage on hematoxylin and eosine (H&E), tartrate-resistant acid phosphatase (TRAP) and toluidine-blue stained paw sections. We performed correlation studies between gait parameters and the histopathological components as well as clinical signs. Results: We identified several gait parameters among them weight bearing, stride length and contact area of the paw to be significantly decreased in hTNFtg animals compared to sex- and age-matched wildtype animals. Moreover, we found a marked reduction in maximum intensity, an indicator for weight bearing, in week 10 and 15 compared to week 6 old hTNFtg mice. Similar effects were seen in print width, print area, print length, max contact max intensity and max contact area at different stages of disease. Interestingly, analgesic treatment with diclofenac (50 mg/kg, i.p.), resulted in a better improvement of weight-bearing parameters in 10 week old hTNFtg mice than in 15 week old hTNFtg animals indicating an pain independent, irreversible functional impairment in progressed disease. To further investigate to which extend synovial inflammation, subchondral bone erosion or cartilage damage are responsible for the functional impairment of joints, we correlated these components with changes in different gait parameters. We observed strong correlations of various gait parameters with the amount of cartilage damage, whereas subchondral bone erosions correlated to a lesser extend and synovial inflammation did not correlate at all. In addition, anti-TNF treatment starting at early stage (6 weeks) or progressed disease (10 weeks) markedly improved clinical as well as histopathological signs and reversed gait changes. Conclusions: Video-based Catwalk gait analysis is a useful tool for quantitative assessment of functional impairment in inflammatory, destructive arthritis. Joint destruction due to cartilage damage but not synovial inflammation per se is the most important component leading to functional impairment of hTNFtg mice.